The Influence of Gen-Z Lifestyle and Parents' Socioeconomic Status on Personal Financial Management with Locus of control as Mediation - Dyah Ayu Weka Resti; Suci Rohayati (STKIP Taman Siswa Bima, 2025)
This research is motivated by students who have taken finance-related courses but are not yet able to optimally manage their finances due to the contemporary Gen-Z lifestyle and their parents' socioeconomic conditions. This study aims to analyze the influence of Gen-Z lifestyle and parents' socioeconomic status on students' personal financial management, with locus of control as a mediating variable. This research uses a quantitative method. The research population consists of students from the Accounting Education Study Program at the Faculty of Economics and Business, Surabaya State University, who have completed the Financial Management or Intermediate Financial Accounting 1 courses, specifically from the 2021, 2022, and 2023 cohorts. Through the Slovin formula, the sample obtained amounted to 194 students using purposive sampling. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The research results indicate that the Gen-Z lifestyle does not significantly affect students' personal financial management, while parental socioeconomic status has a positive and significant impact on students' personal financial management. Locus of control has also been proven to mediate the relationship between independent variables and personal financial management.